Az önkormányzati intézményrendszer átalakulásának lehetséges irányai - Finta, István (Tér és Társadalom, 1996)
The reform of the state budget, the formation of non-profit organisations and the unfavourable economic situation of local governments and their institutions raise many problems which have not been so sharp before, this way evading the attention of the experts. The purpose of the study is to show, with the help of empirical researches, the problems which are generally typical of the most important institutions of local governments. A medium sized and a small town with a small population, also four villages with varying numbers of population were examined, with respect to the expenditure and everyday operation of their local governments and institutions. According to our findings, most of the problems can be seen in the financing and utilisation of small regional institutions and the ownership interests of the local governments concerned. This phenomenon shows that in small regional provision, the agreement of the local governments and a more efficient division of labour should be achieved by central financing techniques and regulation.